Introduction to the Theme Issue: The Global Face of Christian Higher Education - Logan, Jerry (Christian scholar's review, 2013)
Jerry Logan is the Academic Programs Coordinator at Gordon College. Janel Curry is the Provost at Gordon College. This special edition of the Christian Scholar’s Review aims to broaden our understanding of the global face—the contexts, opportunities, and challenges—of Christian higher education.